Inequity in Child Mental Healthcare Use - Nicole Black; David W. Johnston; Michael A. Shields; Trong-Anh Trinh (Institute of Labor Economics (IZA), 2024)
We study the extent of horizontal inequity in children's mental healthcare use in Australia, where universal insurance aims to provide equitable access to needed treatment, regardless of ability to pay. We use linked longitudinal survey data and administrative records that measure the need for mental healthcare - via screening questionnaires and general practitioner (GP) diagnosis - and use of mental health professionals and medication. Using between- and within-child approaches, we find that conditional on need, children from lower income families are significantly less likely to receive services from clinical psychologists than children from higher income households. However, we see little evidence of income inequities in receiving mental health services from GPs or general psychologists. We show that differences in out-of-pocket fees are a likely explanation. The findings highlight that specific support to low-income families is needed to reduce inequities in accessing a complete range of mental health services.
Keywords: I12; I14; 330; child mental health; mental health treatment; unmet mental health need; horizontal inequity; income inequity